3x(-1x+6)=18

Simple and best practice solution for 3x(-1x+6)=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(-1x+6)=18 equation:


Simplifying
3x(-1x + 6) = 18

Reorder the terms:
3x(6 + -1x) = 18
(6 * 3x + -1x * 3x) = 18
(18x + -3x2) = 18

Solving
18x + -3x2 = 18

Solving for variable 'x'.

Reorder the terms:
-18 + 18x + -3x2 = 18 + -18

Combine like terms: 18 + -18 = 0
-18 + 18x + -3x2 = 0

Factor out the Greatest Common Factor (GCF), '3'.
3(-6 + 6x + -1x2) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-6 + 6x + -1x2)' equal to zero and attempt to solve: Simplifying -6 + 6x + -1x2 = 0 Solving -6 + 6x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 6 + -6x + x2 = 0 Move the constant term to the right: Add '-6' to each side of the equation. 6 + -6x + -6 + x2 = 0 + -6 Reorder the terms: 6 + -6 + -6x + x2 = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -6x + x2 = 0 + -6 -6x + x2 = 0 + -6 Combine like terms: 0 + -6 = -6 -6x + x2 = -6 The x term is -6x. Take half its coefficient (-3). Square it (9) and add it to both sides. Add '9' to each side of the equation. -6x + 9 + x2 = -6 + 9 Reorder the terms: 9 + -6x + x2 = -6 + 9 Combine like terms: -6 + 9 = 3 9 + -6x + x2 = 3 Factor a perfect square on the left side: (x + -3)(x + -3) = 3 Calculate the square root of the right side: 1.732050808 Break this problem into two subproblems by setting (x + -3) equal to 1.732050808 and -1.732050808.

Subproblem 1

x + -3 = 1.732050808 Simplifying x + -3 = 1.732050808 Reorder the terms: -3 + x = 1.732050808 Solving -3 + x = 1.732050808 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 1.732050808 + 3 Combine like terms: -3 + 3 = 0 0 + x = 1.732050808 + 3 x = 1.732050808 + 3 Combine like terms: 1.732050808 + 3 = 4.732050808 x = 4.732050808 Simplifying x = 4.732050808

Subproblem 2

x + -3 = -1.732050808 Simplifying x + -3 = -1.732050808 Reorder the terms: -3 + x = -1.732050808 Solving -3 + x = -1.732050808 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = -1.732050808 + 3 Combine like terms: -3 + 3 = 0 0 + x = -1.732050808 + 3 x = -1.732050808 + 3 Combine like terms: -1.732050808 + 3 = 1.267949192 x = 1.267949192 Simplifying x = 1.267949192

Solution

The solution to the problem is based on the solutions from the subproblems. x = {4.732050808, 1.267949192}

Solution

x = {4.732050808, 1.267949192}

See similar equations:

| 7a^2-14a-21= | | 2h-6/6=.5 | | 3(x-1)-4=4(1+x)+5 | | (-1x+6)=18 | | -10+5x+49+90=180 | | 1-4X=7-25 | | (8w+3)(5w-15)=0 | | (5z+8)(2-z)=0 | | -35+5x=x+77 | | 4a^2-12a+8= | | 112c-3= | | 8x+3=8x+72 | | 5(x+5)=5(x+.6) | | 60+30x+90=180 | | f(x)=x^2-10x-4 | | 13k-4= | | n+8+2(n+4)=64 | | 9x+6y=25 | | 5*n=-30 | | 4x+3=-13-4x | | -4p+3(6-4p)=-94 | | 2x^2-8x+1=y | | 11x-7y=-4 | | 3n+2+4n+3=47 | | 30=-4.9t^2+27t+2.4 | | 2(x+5)-4=3x+10 | | 90+x+44++55=180 | | 4-7y=11-4.2y | | 12=-2x+4 | | -131+10x=-2x+121 | | x^2+4x-7=y | | 120=-4(-8x-6) |

Equations solver categories